Модель системи формування творчо спрямованої особистості старшого дошкільника у позашкільному навчальному закладі - Семенов, Олександр; Semenov, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2016)
На підставі авторської концепції дослідження, автором представлено модельне проектування системи формування творчо спрямованої особистості старшого дошкільника у позашкільному навчальному закладі. Під поняттям «система формування творчо спрямованої особистості» автор статті розуміє упорядковану сукупність структурних (цілі, зміст, засоби педагогічної взаємодії суб’єктів освітнього процесу і технології, що реалізуються в спеціально створених сприятливих педагогічних умовах позашкільного навчального закладу; педагогічна оцінка) і функціональних (цілепрогностичний, змістово-контекстний, технологічний, рефлексивно-оцінний) компонентів, що забезпечують формування творчо спрямованої особистості старшого дошкільника. Окрема увага приділяється діяльності суб’єктів навчально-виховного процесу позашкільного навчального закладу. Автор заперечує практику розвитку дітей на основі споглядання за творчістю, де дитина наслідує дії дорослого. В якості альтернативи обґрунтовується підхід активного включення дитини у творчий процес на основі урахування вікових особливостей старшого дошкільника та залучення батьків, як важливого чинника забезпечення психолого-педагогічної підтримки процесу становлення творчо спрямованої особистості. The model of the system of forming creatively directed personality of senior preschooler in out-of-school educational institution that is proposed in the article is based on the author's research concept. The singled notion “system of forming creatively directed personality” the author understands as an ordered totality of structural (objectives, contents, pedagogical means interaction) educational process and technologies that are implemented in specially created favorable conditions of out-of-school educational institution; pedagogical evaluation) and functional (purpose and prognostic, semantic and contextual, technological, reflective and evaluative) components which provide the forming creatively directed personality of senior preschooler. The model which is presented in the article considers the interdependence of subject and environment. Enrichment and improvement of the educational environment of out-of-school educational institution provides the development enrichment of the personality of senior preschooler as the subject thanks to those cultural values and meanings, which it is filled. Special attention is paid to the activities of subjects of the educational process of out-of-school educational institution. The author denies the practice of children development based on contemplation for creativity, where the child imitates the actions of adults. As an alternative approach is substantiated active involvement of the child in a creative process based on senior preschooler age-appropriate and involvement of parents as an important factor in providing psychological and pedagogical support for the process of becoming creatively directed personality.
Model of the system of forming creatively directed personality of senior preschooler in out-of-school educational institution
Keywords: модель системи формування творчо спрямованої особистості старшого дошкільника; позашкільний навчальний заклад; the model of the system of forming creatively directed personality of senior preschooler; out-of-school educational institution